An Analysis and Evaluation of the Polish Cutter Fishery on the Baltic Sea in the Years 1971–2001. Fleet, Catch, Results - Kubicki, Mateusz (Vade Nobiscum, tom XXI/2019: Studia z historii gospodarczej, kulturowej i społecznej, 2019)
The objective of the article is to present Polish national fishery on the Baltic Sea in the years 1971–2001. During this period, significant changes of the examined industry occurred, along with its thorough modernisation that ended in practice only in 1992, featured extremely variable fishing results. Finally, the beginning of privatization process in 1989 caused immense marginalisation of fishing, changing its ownership structure for ever. These changes affected mainly national fishing combined collectives and cooperatives that formed peculiar pillars of the national fishing on the Baltic Sea. The first part of article presents issues related to the number of fleet vessels of national businesses and cooperatives, completed modernisations, and it investigates structures of fleets considering averaged power [HP] and buoyancy [GT]. The second part presents issues related to catches. Among the most important factors that have already been analysed are the total volume of raw material acquisition, division of results between combined collectives and cooperatives, share of particular national businesses in catches and averaged results obtained by particular share classes. The last part discusses matters related to averaged fishing results in tones converted into power [HP] and in tones into buoyancy [GT]. An additional supplement is an indication of averaged results per total employment in examined entities, converted into the number of fishermen.